Personen- und Güterbahnhöfe. Kurzer Abriss aus betrieblicher Sicht. - Häßler, Michael; Hildebrand, Wolf-Christian (Deutscher Verkehrs-Verl., 2010)
Der Personen- und der Güterverkehr auf der Schiene haben gemeinsame Wurzeln. In den nunmehr 175 Jahren deutscher Eisenbahngeschichte haben sich die beiden Formen des Verkehrs jedoch ganz unterschiedlich entwickelt. Beobachten lassen sich diese unterschiedlichen Entwicklungspfade insbesondere an den Bahnhöfen des Personen- und Güterverkehrs seit der Mitte des 19. Jahrhunderts bis in die Neuzeit.

Carrying on from the initially close integration of passenger and freight transport, the more profound differentiation among means of transport has given rise to different types of railway stations. The predominant ones are the transit station (and stop) for passenger traffic, the shunting yard for freight trains composed of single wagons, and the KV-terminal for combined transport, At present, stations are commonly affected by the termination, to a large degree, of costly railway-specific types of manoeuvres (i.e. shunting and de- or re-coupling of freight wagons, engine changes) or their concentration on a few - but often large - railway stations. By taking railways' operational aspects into account, efficiency-related assessments have emerged as the essential starting point for station design. Urban development schemes should, nonetheless, also be given due consideration.
Designing passenger and freight railway stations.
Keywords: Verkehr; Güterverkehr; Personenverkehr; Eisenbahn; Bahnhof; Güterbahnhof; Hauptbahnhof; Rangierbahnhof; Abfertigung; Verkehrsgeschichte; Eisenbahngeschichte; Bahnhofsgebäude; Kopfbahnhof; Durchgangsbahnhof